Rancang Bangun Sistem Pendataan Sumbangan Pembinaan Pendidikan (SPP) dengan Integrasi Notifikasi SMS Gateway Pada SMK YPT Pringsewu - Adi Setia Nugraha; Didik Kurniawan (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
SPP or commonly known as the Education Development Contribution is a cost fund that is charged to students to help the process of educational institutions facilitate the teaching and learning process. SPP is a form of regular student tuition which is paid once a month and is a form of commitment for every student who is still active in school. The SPP payment system at SMK YPT Pringsewu is currently done conventionally by recording on the SPP card. The process of SPP payment transactions is recorded in the general ledger. The lack of information on tuition payments from the school to the parents/guardians of students has an impact on the data collection system for regular student fees to the school. The development of a data collection information system for Educational Development Contributions (SPP) was made to facilitate the management of tuition payments. Added notification feature via SMS gateway sent to parents/guardians of students at SMK YPT Pringsewu. The method used is the Waterfall method, developed using the PHP programming language and MySQL database. The existence of an information system for collecting data on the contribution of education development (SPP) at SMK YPT Pringsewu, is expected to help the administrative process of paying tuition fees to be more efficient and effective.